Possibilities of vaginal biotope correction in pregnant women after application of auxiliary reproductive technologies - L.M. Vygivska; V.O. Beniuk; I.V. Maidannyk; I.A. Usevych; L.D. Lastovetska; Y.G. Drupp; V.V. Kurochka (Publishing House TRILIST, 2021)
Research objective: to determine the role and effectiveness of the proposed therapeutic and prophylactic complex in the correction of vaginal biocenosis disorders in the dynamics of pregnancy in pregnant women after assisted reproductive technologies (ART) to improve the tactics of antenatal observation and prevention of obstetric and perinatal complications. Materials and methods. 299 pregnant women were examined: the main group included 249 women with pregnancy after ART, the control group consisted of 50 pregnant women with spontaneous pregnancy. Therapeutic and prophylactic measures for pregnant women after ART included: micronized progesterone, magnesium oxide, folic acid, L-arginine aspartate, ω-3-polyunsaturated fatty acids, long-term psychological correction (on the eve of the ART program, at 8-10 weeks, 16-18 weeks and 28-30 weeks of pregnancy). The drug for antibiotic therapy for local sanitation of the genital tract was chosen taking into account the sensitivity to antibiotics of certain microbial associates and was prescribed for 7-10 days. At the second stage of sanitation of the genital tract probiotics were prescribed under the control of pH-metry to maintain the acidic environment of the vaginal contents, colonize the vagina and the vaginal part of the cervix with lactobacilli. Results. There was a significant decrease in the proportion of women with a large number of epithelial cells in the main groups, which are a sign of alterative inflammation, and this is coincides with a similar indicator in the control group. Women with moderate leukocyte count and mixed Gram-negative microflora prevailed in IB, IIB and IIIB subgroup, who received conventional therapy. There was no significant difference in IIIA and IIIB subgroups. In the vaginal biocenosis significantly increased the Lactobacillus spp. content against the background of probiotics with local and general action in ІА, ІІА and ІІІА subgroups. The average Lactobacillus spp. concentration was significantly different from the average indicators of subgroups receiving conventional therapy for vaginal sanitation, with a significant decrease in the biocenosis of aerobic and anaerobic microorganisms and Candida albicans, which indicates the effectiveness of the proposed two-stage treatment. Conclusions. The proposed improved two-stage sanitation of the genital tract with a selective probiotic against the background of long-term progesterone and magnesium support ensures the stabilization of the vaginal pH at the physiological level corresponding to the normocenosis, and contributes to a significant increase in Lactobacillus spp. within the physiological norm with a significant decrease of Candida albicans concentration in the biotope, as well as opportunistic pathogens of aerobic and anaerobic origin. This is provides conditions for the prolongation of pregnancy in women after ART treatment cycles.